Targeting of Basophil and Mast Cell Pro-Allergic Reactivity Using Functionalised Gold Nanoparticles - Yasinska, Inna M.; Calzolai, Luigi; Raap, Ulrike; Hussain, Rohanah; Siligardi, Giuliano; Sumbayev, Vadim V.; Gibbs, Bernhard F. (Frontiers in Pharmacology, 2019)
Calcineurin inhibitors potentially prevent pro-allergic mediator release from basophils and mast cells but are rarely used systemically due to ubiquitous expressions of target signalling proteins. However, specific targeting of allergic effector cells with these inhibitors could circumvent unwanted side effects. We recently demonstrated the biocompatibility of gold nanoparticles (AuNPs) as a platform for non-toxic delivery of signalling inhibitors due to unique physicochemical properties of these nanomaterials. Since AuNPs can be conjugated with both anti-allergic drugs and antibodies or other proteins that specifically recognize basophils and mast cells, our aims were to assess specific targeting of allergic effector cell function using AuNPs conjugated with the calcineurin inhibitor ascomycin. Purified human basophils and LAD2 human mast cells were used for investigations with AuNPs conjugated either to CD203c antibodies or containing stem cell factor (SCF), respectively, which were amine-coupled to acidic groups of reduced glutathione (GSH). GSH was also used as a spacer for immobilisation of ascomycin on the gold surface. AuNPs conjugated with anti-CD203c and ascomycin strikingly blocked IgE-dependent degranulation of both purified basophils and those present in mixed leukocyte preparations, suggesting specific targeting of these cells. In contrast, LAD2 mast cell responses were not inhibited using anti-CD203c-containing nanoconjugates but were when the conjugates contained SCF. Successful targeting of allergic effector cells using gold nanoconjugates indicates that this technology may have therapeutic potential for the treatment of allergies by specifically delivering highly effective signalling inhibitors without side-effects.